SIKAP MENYALAHKAN DIRI DALAM DES VENTS CONTRAIRES KARYA OLIVIER ADAM - Vaneta, Ramadhela; Bandu, Irianty (JURNAL ILMU BUDAYA, 2025)
The purpose of this study is to describe the attitude of self-blame and analyze the meaning of life in the novel Des Vents Contraires by Olivier Adam. This study uses a qualitative descriptive method with a literature study approach. Based on the results of the analysis in this study, it can be concluded that 1) The depiction of Paul Anderson's family life depicts a complex and evolving emotional journey that occurs after the tragic loss of Sarah, from initial confusion to a willingness to move on with the understanding that they must continue living, even with a deep sense of loss. 2) The attitude of self-blame in the character Paul Anderson is reviewed by theory according to Zuama (2011), guilt or self-blaming is a relevant aspect in understanding how Paul handles conflicts between unconscious drives.